Shortcomings of MRP II and a new planning meta-method - Alf Kimms; Andreas Drexl (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 1996)
Lot sizing when done for the short-term heavily interacts with the sequencing decisions for the operations to be performed. Especially for real-world situations where capacities are scarce, demand is dynamic, and precedence relations among the operations have to be taken into account the MRP II logic which is implemented in most production planning systems does not satisfy. In this paper, we will reveal the shortcomings of MRP II by means of an example. A mixed-integer programming model is then defined to specify the problem of capacitated, dynamic, multi-level Iot sizing and scheduling. Also, we present a generic solution method (a so-called meta-method) which may be used as a basis of more advanced implementations that may replace the traditional MRP II Systems.
Keywords: 650